Presentation of the dental management of a patient with mental disability - Martínez, María; Pérez, Edgar; Badillo, Bitia (Revista Acciones Médicas, 2022)
Disability refers to impairments, activity limitations, and participation restrictions. Severe or serious difficulties in walking (64.1%) and seeing (58.4%) are the most frequent in both men and women, and the least reported are speaking or communicating (18%), being higher in men. The objective of this article was to determine the experience of hygiene and caries control, as well as to know the impact of restoring function and satisfaction of patients with mental disabilities. A male patient was presented to the FEBUAP pediatric dentistry clinic in conditions of abandonment and mental disability where the reason for consultation was dental pain on chewing. Multiple caries lesions, root remains, poor hygiene conditions and personal neglect, gingivitis and tartar were observed. Prophylaxis, extractions, restorations with amalgam and resin were performed, an impression was taken for a definitive upper and lower total removable prosthesis. It was concluded that oral health has a great influence on the functioning and quality of life of people with disabilities, which can be further aggravated by diseases of other organs and systems. In addition, poor oral health is a public health problem for the population and mainly affects people with mental disabilities.
Keywords: disability; mental retardation; treatment; psychosocial intervention